2009
DOI: 10.1111/j.1471-4159.2009.06389.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuro‐inflammation induced in the hippocampus of ‘binge drinking’ rats may be mediated by elevated extracellular glutamate content

Abstract: The neuropathological and immune changes induced in the brain by ‘binge drinking’ have been investigated in a rat model. Evidence of neuro‐inflammation was identified in the ‘binge drinking’ rat model of alcohol abuse after 3 weeks of administration of 2 or 3 g/kg ethanol (EtOH), three times per day for two consecutive days, followed by 5 days of abstinence: Firstly, alveolar macrophages, isolated from these animals, showed significant increases in inducible nitric oxide synthase, as assayed by nitrite release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 43 publications
3
82
1
1
Order By: Relevance
“…At the production conditions used here (15.000 IMA/cm 2 ), we examined whether the composition of conditioned medium changed drastically. As elevated extracellular L-glutamate (L-Glu) content has been reported in previous inflammation models (Castillo et al 2002;Ward et al 2009), we also investigated whether this could be the cause of neurotoxicity in our model. Amino acid analysis showed that cytokine-conditioned medium differed for few amino acids from control supernatant, but many constituents, including L-Glu, remained largely unchanged (Fig.…”
Section: Neurotoxicity Triggered By Activated Glia Through the Activimentioning
confidence: 99%
“…At the production conditions used here (15.000 IMA/cm 2 ), we examined whether the composition of conditioned medium changed drastically. As elevated extracellular L-glutamate (L-Glu) content has been reported in previous inflammation models (Castillo et al 2002;Ward et al 2009), we also investigated whether this could be the cause of neurotoxicity in our model. Amino acid analysis showed that cytokine-conditioned medium differed for few amino acids from control supernatant, but many constituents, including L-Glu, remained largely unchanged (Fig.…”
Section: Neurotoxicity Triggered By Activated Glia Through the Activimentioning
confidence: 99%
“…Additionally, experimental studies demonstrate that binge drinking increases inflammation levels as well as insulin resistance (9,10). Inflammation and insulin resistance are hypothesized to be key biological mechanisms for the development of cancer, and thus binge drinking could be particularly relevant for breast cancer risk (11).…”
mentioning
confidence: 99%
“…The ethanol intoxication causes an increase in the microglial biomarkers (Crews et al, 2006;He and Crews, 2008;Ward et al, 2009) which can be activated in a neuroprotective way (Zhao et al, 2012), lastly reducing the apoptotic damage (Lalancette-Hebert et al, 2007). Our study provides evidence that the chronic ethanol intake can cause apoptotic responses in the glial cells leading to a microenvironmental imbalance, and consequently allowing the axons to be severely affected by degradation because of slow axonal transmission and low neuronal capacity.…”
Section: Discussionmentioning
confidence: 66%